Teacher's Work Spirit (Causal Model Of Extroversy Personality, Emotional Intelligence And Job Satisfaction On The Work Spirit Of Medan City State Madrasah Aliyah Teachers) - Hadi, Riswan; Rafida, Tien; Hadijaya, Yusuf (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research aims to determine: (1) the influence of extroverted personality on job satisfaction; (2) the influence of emotional intelligence on job satisfaction; (3) the influence of extroverted personality on teacher morale; (4) the influence of emotional intelligence on teacher morale; and (5) the influence of job satisfaction on teacher morale. Subject study is Medan City State Madrasah Aliyah teachers with a total sample size 184 people. Taking sample done with proportional simple random sampling. Method study nature path analysis which aims to test theory and obtain information about research. Based on testing hypothesis can be concluded: (1) exists influence straight extroverted personality with job satisfaction of 0.03 (3%); (2) exists influence direct emotional intelligence with job satisfaction of 0.05 (5%); (3) exists influence direct extroverted personality with teacher's enthusiasm for work of 0.02 (2%); (4) exists influence direct emotional intelligence with teacher's enthusiasm for work amounted to 0.07 (7%); and (5) exist direct influence job satisfaction on teacher morale as big as 0.01 (1%). The research results provide an overview of personality Extroversion, emotional intelligence, and job satisfaction influence teacher morale by 20% and the rest is determined by other circumstances.